A Review of Persian-Language Articles Published in The Field of Medical Education - Mohammad Fakhari; Tahereh changiz; Alireza yousefy (مجله ایرانی آموزش در علوم پزشکی, 2017)
Introduction: Review of published research in the field of medical education helps determine the direction of future research. The aim of this study was to perform a quantitative content analysis of Persian language articles published in the field of medical education during 2014. Methods: In this study, all articles published in nine scientific journals in the field of medical education during 2014 were reviewed. The variables were extracted from the full-text of articles including title, the number of authors, type of article, research methodology, sample size, research population and topics. The collected data were analyzed using descriptive statistics. Results: A total of 366 articles were analyzed. In the titles of articles, 97% of the articles referred to research variable, 41% to research methodology and research population, and 13% to research intervention. Also, 39% of the articles referred to the site and 11% to the time of the research. 42% of articles were descriptive. The most common topics were teaching methods, student health status and thinking style. Conclusion: This study focused on the analysis of published articles during a one-year period. Qualitative and quantitative analyses of publications in later years would provide the necessary information for research and educational policy-making in medical education.